The Politics of Law of Sharia Economics in Indonesia - Hasbi Hasan; Cecep Mustafa (APPTHI, 2022)
This study examines the process of institutionalization of sharia principles in the economic field, along with the process of legislation and regulation in the national legal system. The scope of this study will rely on the existence, opportunities, and challenges of actualizing the Islamic economic system from the perspective of Indonesian legal politics. Specifically, this approach is carried out based on the authority of Islamic law and its existence as a source of law in Indonesia’s national legal order, with a sharp level of attention to the dynamics of regulatory policies on sharia economic business activities. Starting from the characteristics of Indonesian political legalism under the umbrella of the 1945 Constitution, which adheres to the concept of “unification and codification in a “unique way,” the study of sharia economics in Indonesian legal politics has also given birth to several knots that are “unique.” Theoretically, the concept of “unification” is a way for national legal politics to shape law in the condition of a pluralistic Indonesian nation. One principle that is used as a theoretical benchmark in this regard is how to carry out the process of legal unification in a pluralistic society that seeks to maintain a process of differentiation in a sustainable manner of sharia economics. Abstrak Penelitian ini menyoroti proses pelembagaan prinsip syariah dalam bidang ekonomi berikut proses legislasi dan regulasinya dalam sistem hukum nasional. Lingkup kajian ini akan bertumpu pada eksistensi, peluang dan tantangan aktualisasi sistem ekonomi syariah dalam perspektif politik hukum Indonesia. Secara spesifik, pendekatan ini dilakukan dengan bertolak pada otoritas hukum Islam dan eksistensinya sebagai sumber hukum dalam tertib hukum nasional Indonesia, dengan tingkat perhatian yang tajam pada dinamika kebijakan regulasi atas kegiatan usaha ekonomi syariah. Bertolak dari karakteristik legalisme politik hukum Indonesia di bawah payung UUD 1945 yang menganut konsep”unifikasi dan kodifikasi secara “unik,” kajian tentang ekonomi syariah dalam politik hukum Indonesia juga telah melahirkan beberapa kata simpul yang bersifat “unik.” Konsep “unifikasi” secara teoritik merupakan satu jalan bagi politik hukum nasional untuk membentuk hukum dalam kondisi bangsa Indonesia yang majemuk. Salah satu prinsip yang dijadikan tolak ukur teoritis dalam hal ini adalah bagaimana melakukan proses penyatuan hukum dalam masyarakat majemuk yang berupaya mempertahankan proses diferensiasi ekonomi syariah secara berkelanjutan. Kata kunci: Politik Hukum, Ekonomi Syariah, Kerangka Hukum, Indonesia